Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1982
DOI: 10.1083/jcb.95.1.340
|View full text |Cite
|
Sign up to set email alerts
|

Localization of type IV collagen, laminin, heparan sulfate proteoglycan, and fibronectin to the basal lamina of basement membranes.

Abstract: Electron microscopic immunostaining of rat duodenum and incisor tooth was used to examine the location of four known components of the basement-membrane region: type IV collagen, laminin, heparan sulfate proteoglycan, and fibronectin. Antibodies or antisera against these substances were localized by direct or indirect peroxidase methods on 60-/~m thick slices of formaldehyde-fixed tissues.In the basement-membrane region of the duodenal epithelium, enamel-organ epithelium, and blood-vessel endothelium, immunost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
182
2
4

Year Published

1983
1983
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 435 publications
(197 citation statements)
references
References 43 publications
9
182
2
4
Order By: Relevance
“…The labelling obtained over the basal laminae of normal animals was found to be restricted to the central laminae densa of the basal laminae and this was supported by morphometrical evaluation. These observations confirm previous results obtained by applying the immunoperoxidase and immunoferritin techniques [16][17][18][19]. However, compared with these previous studies in which diffusion is a problem [37], the localization obtained applying the protein A-gold technique appears to be of higher specificity and resolution.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The labelling obtained over the basal laminae of normal animals was found to be restricted to the central laminae densa of the basal laminae and this was supported by morphometrical evaluation. These observations confirm previous results obtained by applying the immunoperoxidase and immunoferritin techniques [16][17][18][19]. However, compared with these previous studies in which diffusion is a problem [37], the localization obtained applying the protein A-gold technique appears to be of higher specificity and resolution.…”
Section: Discussionsupporting
confidence: 90%
“…These antibodies were raised in sheep using an antigen extracted from the mouse EHS tumor and purified by salt precipitation and ion exchange chromatography [33,34]; they react with basal laminae of various animal tissues and in particular with rat glomerular basal laminae [16,18], and their high specificity has been demonstrated previously using several approaches [16,18,35]. To locate type IV collagen, the protein A-gold immunocytochemical postembedding approach was applied [25].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several protein components of basement membranes have been identified (4). Type IV collagen appears to be restricted to the lamina densa (5-7), whereas laminin, fibronectin, and heparan sulfate proteoglycan are present in either the lamina lucida or lamina densa (5,(7)(8)(9)(10)(11)(12). We have shown that antibodies to type IV collagen, laminin, and the thymocyte differentiation antigen Thy-1 stain the basement membrane in the mammary glands of both virgin and lactating rats at the light microscope level, whereas antibodies to fibronectin only stain the basement membrane in the mammary gland of lactating rats (1,13,14).…”
mentioning
confidence: 99%
“…chondroitin sulfate and keratan sulfate) and are secreted by cells to create their extracellular niche (Humphries et al 2006). Non-ECM ligands include counter-receptors (ICAMs and VCAMs), plasma proteins (fibrinogen and von Willebrand factor), complement factors, cytokines and pathogens (viruses, bacteria and toxins) (Laurie et al 1982;Humphries et al 2006).…”
Section: Integrin Ligandsmentioning
confidence: 99%